ANALISIS INOVASI KETENAGAAN PENDIDIKAN DALAM PENGEMBANGAN PROFESIONALISME GURU DI SDN 3 SUKAJAYA - Silmi Hidayati; Dani Gunawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze educational workforce innovation in developing teacher professionalism at SDN 3 Sukajaya and to identify the challenges faced in its implementation. Teacher professionalism is an essential factor in improving the quality of education because teachers play a strategic role in the learning process and in shaping students' character. Therefore, innovative efforts in managing educational personnel are necessary to help teachers improve their competencies and adapt to the dynamic development of education. This research employed a qualitative research method with a descriptive approach. The data sources consisted of primary and secondary data. Primary data were obtained through interviews with the principal and teachers, while secondary data were collected from school documents related to teacher professional development programs. Data collection techniques included observation, interviews, and documentation. The data were analyzed using descriptive qualitative analysis through the processes of data reduction, data presentation, and conclusion drawing.The results of the study indicate that educational workforce innovations implemented at SDN 3 Sukajaya include the organization of regular training and workshops for teachers, the utilization of technology in the learning process, and the establishment of a teacher professional development team. These innovations aim to enhance teachers’ competencies, performance, and professionalism in conducting the learning process. However, several challenges were identified in the implementation, including limited educational facilities and infrastructure, resistance from some teachers to changes, limited time for teachers to participate in professional development activities, and the lack of continuous evaluation of development programs. In conclusion, educational workforce innovation plays an important role in supporting the development of teacher professionalism. However, it requires adequate resources, teachers’ readiness to adapt to change, and a sustainable evaluation system to ensure its optimal implementation.